Features of Development Marketing Strategy in the Conditions of Economy Modernization. Example of the Dairy Industry of Almaty - TEKENOV, Agzam; BAIMAGAMBETOVA, Lyazzat; TEKENOV, Uzak; DAURENBEKOVA, Asima (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
The milk and dairy products market, being an important component of the agri-food market, is a complex and dynamically developing economic system of relations between its business entities. In recent years, both in Kazakhstan as a whole and in the Almaty region, there has been a mixed trend in the production and consumption of milk and dairy products. The timeliness and relevance of research related to the search for effective methods and tools that contribute to the formation of a rational development strategy for dairy enterprises is determined by the need for practical application of management theory tools and a process-oriented approach, which will allow implementing a mechanism for end-to-end management of the enterprise’s production business processes. The use of this toolkit will allow dairy enterprises to adapt to constantly changing environmental factors and ensure the formation of a sustainable development mechanism for the industry